Pharmacotherapy for diabetic peripheral neuropathy pain and quality of life: A systematic review. (16th May 2017) - Waldfogel, Julie M.; Nesbit, Suzanne Amato; Dy, Sydney M.; Sharma, Ritu; Zhang, Allen; Wilson, Lisa M.; Bennett, Wendy L.; Yeh, Hsin-Chieh; Chelladurai, Yohalakshmi; Feldman, Dorianne; Robinson, Karen A.
Abstract : Objective: To systematically assess the effect of pharmacologic treatments of diabetic peripheral neuropathy (DPN) on pain and quality of life. Methods: We searched PubMed and Cochrane Database of Systematic Reviews for systematic reviews from 2011 to October 12, 2015, and PubMed, Embase, and the Cochrane Central Register of Controlled Trials for primary studies from January 1, 2013, to May 24, 2016. We searchedClinicaltrials.gov on March 9, 2016. Two reviewers independently evaluated studies for eligibility, serially abstracted data, and independently evaluated risk of bias and graded strength of evidence (SOE). Results: We updated a recently completed systematic review of 57 eligible studies with 24 additional published studies and 25 unpublished studies. For reducing neuropathy-related pain, the serotonin-norepinephrine reuptake inhibitors duloxetine and venlafaxine (moderate SOE), the anticonvulsants pregabalin and oxcarbazepine (low SOE), the drug classes tricyclic antidepressants (low SOE) and atypical opioids (low SOE), and botulinum toxin (low SOE) were more effective than placebo. We could not draw conclusions about quality of life due to incomplete reporting. All studies were short-term (less than 6 months), and all effective drugs had more than 9% dropouts from adverse effects. Conclusions: For reducing pain, duloxetine and venlafaxine, pregabalin and oxcarbazepine, tricyclic antidepressants, atypical opioids, and botulinum toxin were more effective than placebo. However, quality of life was poorly reported, studies were short-term, drugs had substantial dropout rates, and opioids have significant risks. Future studies should evaluate longer-term outcomes, use methods and measures recommended by pain organizations, and assess patients' quality of life.